Readiness to Change as a Predictor of Treatment Engagement and Outcome for Partner Violent Men - Maldonado, Ana I. (Journal of interpersonal violence, 2021)
Resistance to change has been long recognized as a barrier to successful intervention for partner violent individuals. Using archival data from a community-based intimate partner violence (IPV) intervention program, the current study investigated readiness to change as a predictor of treatment engagement and outcome in cognitive behavioral therapy (CBT) for IPV, and examined whether court referral status, antisocial personality characteristics, and borderline personality characteristics moderate these associations. During program intake, male IPV perpetrators (N = 195) provided structured interview data on demographics and referral source, and self-report data on readiness to change, borderline personality traits, and antisocial personality traits. During group CBT, participants and their therapists completed measures of the working alliance, and the therapists completed ratings of compliance with behavior change homework assignments. Criminal recidivism data were gathered from public records for 2 years after scheduled completion of treatment. Readiness to change significantly predicted client ratings of the working alliance, but not therapist ratings of the working alliance, CBT homework compliance, or criminal recidivism. Court referral status moderated predictive associations between readiness to change and working alliance ratings, and borderline and antisocial characteristics moderated predictive associations between readiness to change and working alliance as well as criminal recidivism. Interestingly, readiness to change is a stronger predictor of positive treatment response for court- versus self-referred individuals and for those with either very low or very high levels of borderline and antisocial characteristics. Hence, strategies to enhance motivation to change may be particularly be important for IPV perpetrators with these characteristics.